2012
DOI: 10.1038/nature10812
|View full text |Cite
|
Sign up to set email alerts
|

Piezo proteins are pore-forming subunits of mechanically activated channels

Abstract: Mechanotransduction plays a crucial role in physiology. Biological processes including sensing touch and sound waves require yet unidentified cation channels that detect pressure. Mouse piezo1 (mpiezo1) and mpiezo2 induce mechanically activated cationic currents in cells; however, it is unknown if piezos are pore-forming ion channels or modulate ion channels. We show that Drosophila piezo (dpiezo) also induces mechanically activated currents in cells, but through channels with remarkably distinct pore properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
899
2
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 948 publications
(936 citation statements)
references
References 37 publications
28
899
2
7
Order By: Relevance
“…Importantly, using bilayer reconstitution experiments, it was further shown that Piezo proteins are pore-forming subunits [26]. The function of Drosophila Piezo has recently been shown in mechanical nociception, in line with the role of mouse Piezo2 in pain-sensitive dorsal root ganglion neurons [25,27].…”
Section: Introductionmentioning
confidence: 77%
“…Importantly, using bilayer reconstitution experiments, it was further shown that Piezo proteins are pore-forming subunits [26]. The function of Drosophila Piezo has recently been shown in mechanical nociception, in line with the role of mouse Piezo2 in pain-sensitive dorsal root ganglion neurons [25,27].…”
Section: Introductionmentioning
confidence: 77%
“…As mechanotransductory channels, PIEZO channels form a close functional unit with the plasma membrane (43)(44)(45), also demonstrated by the inhibitory effect of GsMTx4, which acts as a gating modifier that inserts at the channel-lipid interface (32). Against this background, we decided to next test the function of dynamin, recently referred to as "membrane remodeler" (46), on PIEZO mechanotransductory function in chondrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…One example of how this protocol can be adapted to record one channel currents from other ions channels, specifically mouse PIEZO1, a mechanosensitive ion channel, is presented below (Figure 7) 25,26 .…”
Section: Recombinant Piezo1 Channelsmentioning
confidence: 99%